Exploratory Factor Analysis of Regional Economic Development Indicators in Indonesia : A Maqasid Al-Shariah Approach - Elvira, Rini; Izmuddin, Iiz (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study aims to identify the factor structure of regional economic development indicators in Indonesia using Exploratory Factor Analysis and map them into the five dimensions of maqasid al-shariah, namely the protection of faith (din), soul (nafs), intellect (aql), offspring (nasl), and property (mal).Design/methodology: This research uses an explanatory quantitative approach with Exploratory Factor Analysis (EFA) technique on panel data of 34 provinces in Indonesia during the period 2017-2023.Findings: This study found that 12 out of 18 indicators of regional economic development in Indonesia have represented the five dimensions of maqasid al-shariah. This finding was obtained through exploratory factor analysis (EFA) with Promax Rotation, where all indicators had factor loading values ≥ 0.5. This finding confirms the validity of the factor structure as well as its compatibility with the maqasid al-sharia approach.Practical Implication: This study emphasizes the integration of maqasid al-shariah into regional development, ensuring a balance between material and non-material welfare. The framework supports policymakers in reducing disparities and promoting inclusive and sustainable growth.Originality/Value: This research offers a new approach in mapping conventional economic development indicators into the maqasid al-sharia approach through the EFA method, which has not been widely done in shariah economic development studies in Indonesia.